The Creston, California, meteorite fall and the origin of L chondrites. (20th January 2019) - Jenniskens, Peter; Utas, Jason; Yin, Qing‐Zhu; Matson, Robert D.; Fries, Marc; Howell, J. Andreas; Free, Dwayne; Albers, Jim; Devillepoix, Hadrien; Bland, Phil; Miller, Aaron; Verish, Robert; et al.
Abstract: It has been proposed that all L chondrites resulted from an ongoing collisional cascade of fragments that originated from the formation of the 500 Ma old asteroid family Gefion, located near the 5:2 mean‐motion resonance with Jupiter in the middle Main Belt. If so, L chondrite pre‐atmospheric orbits should be distributed as expected for that source region. Here, we present contradictory results from the orbit and collisional history of the October 24, 2015, L6 ordinary chondrite fall at Creston, CA (here reclassified to L5/6). Creston's short 1.30 ± 0.02 AU semimajor axis orbit would imply a long dynamical evolution if it originated from the middle Main Belt. Indeed, Creston has a high cosmic ray exposure age of 40–50 Ma. However, Creston's small meteoroid size and low 4.23 ± 0.07° inclination indicate a short dynamical lifetime against collisions. This suggests, instead, that Creston originated most likely in the inner asteroid belt and was delivered via the ν6 resonance. The U‐Pb systematics of Creston apatite reveals a Pb‐Pb age of 4, 497.1 ± 3.7 Ma, and an upper intercept U‐Pb age of 4, 496.7 ± 5.8 Ma (2σ), circa 70 Ma after formation of CAI, as found for other L chondrites. The K‐Ar (age 4.3 Ga) and U, Th‐He (age 1 Ga) chronometers were not reset at 500 Ma, while the lower intercept U‐Pb age is poorly defined as 770 ± 320 Ma. So far, the three known L chondrites that impacted on orbits with semimajor axes a <2.0 AU all have high (>3 Ga) K‐Ar ages. This argues for a source of some of our L chondrites in the inner Main Belt. Not all L chondrites originate in a continuous population of Gefion family debris stretching across the 3:1 mean‐motion resonance.